Determination of the relative configuration of tropinone and granatanone aldols by using TBDMS ethers - Lazny, Ryszard; Nodzewska, Aneta; Sidorowicz, Katarzyna; Kalicki, Przemyslaw (Beilstein Journal of Organic Chemistry, 2012)
The relative configurations of tert-butyldimethylsilyl (TBDMS) ethers of all four diastereomers of the aldols of tropinone (8-methyl-8-azabicyclo[3.2.1]octan-3-one), as well as of granatanone (9-methyl-9-azabicyclo[3.3.1]nonan-3-one), were determined from NMR data, and from the observed interconversion of the diastereomers (exo,anti to endo,syn and exo,syn to endo,anti). The exo forms invert to endo isomers in the presence of silica gel. The relative configuration of a new isomer of tropinone aldol accessible synthetically through the direct solventless reaction of tropinone and benzaldehyde in the presence of water was determined as exo,syn by comparison of NMR data of the aldol isomers, in particular vicinal coupling constants and shifts corresponding to the side-chain CH group, with data of related TBDMS derivatives and confirmed by single-crystal X-ray diffraction.
Keywords: aldol reaction; exo–endo isomerization; granatanone; stereoselective reaction; tropinone